(untitled) (Research, Society and Development, 2021)
Objectives: to demonstrate the historical series of hospitalizations for sepsis in Brazil, which capitals and regions are most affected, as well as whether these hospitalizations grew and in what proportion they occurred and what is the relationship with the Human Development Index (HDI). Methods: An epidemiological time series study was conducted with data on hospitalizations for septicemia in Brazilian capitals from 1999 to 2016 obtained from the Hospital Information System of the Ministry of Health (SIH) and their HDI in the same period. The hospitalization indicators were calculated for half of each three-year period. Linear and Poisson regression models were performed to verify the temporal tendency and Pearson or Spearman correlation coefficients for correlation with the HDI. Results: there was a significant increase in hospitalizations in some capitals, such as: Boa Vista, Maceió, Porto Velho and Rio de Janeiro, and a decrease in Campo Grande and Goiânia. The highest average of hospitalizations occurred in Porto Velho with 26,443.7 and the lowest average in Teresina 171.3. The correlation coefficients between the total number of hospitalizations and the HDI of each capital, showed a positive and significant increase for Belo Horizonte, Boa Vista, São Paulo and Vitória. Conclusion: hospitalizations for sepsis had more increases than decreases, and the correlation with the HDI showed that the higher the HDI, the greater the hospitalizations, suggesting that with higher rates, it becomes possible to provide an adequate structure and better performance in early recognition and outcome of sepsis.